Gender Construction of Women as Maung Geulis in Indonesian Football - Ariyanto, Ari (Bina Nusantara University, 2017)
Talking about football, we could not separate it from the supremacy of masculinity that was created and rooted powerfully by men. It seemed that football was a sport that could be done merely by men and for men. That perspective became one of the most fundamental reasons why football was destined for men. However, there were a lot of women interested in football and becoming the supporter of the football team. Practically, these women supporters had their own labeling as supporters. It indicated that there was a role of women in football, either as a player or supporter. This study discussed the gender construction as a woman by means of the labeling itself. The qualitative-descriptive method was employed to investigate the women gender construction as ‘Maung Geulis’ in Indonesian football teams’ territory. The result shows how the manifestation of the women supporters in football can gain the motivation of morality to the football players in the field. Moreover, there is a desire of the women to show the gender equality through the labeling of ‘Maung Geulis’ as the women supporters. Either ‘Maung Geulis’ or other women supporters are attempted to locate the role of women in men’s domain. The potential of women as ‘Maung Geulis’ to be equal with men supporters is buried by the different labeling. The issue gives a distance of equality by using the political labeling becomes contra productive in the effort to construct the gender equality.